Analisis Perkembangan Bahasa Anak Usia Dasar (Tercapai) Di MI Ma’arif Sambego - Bella Oktadiana; Esti Hayati; Ira Agus Sofiana (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
This research (article) discusses the Language Development of Basic Children (Reached) in Mi Ma'arif Sambego Yogyakarta. The purpose of this study was to determine the language development of students of elementary age in MI Maarif Sembego. This type of research is descriptive qualitative, the informants of this study were class III students named Shaafira. The data collection tool in this study is in the form of observation, interviews and documentation. While the data that has been collected is then analyzed by descriptive qualitative data analysis techniques, namely data reduction, data presentation and conclusion (verification). The results of his research are the development of the language of children of elementary age (reached) in Mi Ma'arif Sambego Yogyakarta including First phonetics, namely the sound of the language. Both Morphology changes in word form, as well as changes in the form of words to the meaning and class of words. The third Syntax is to sort words in meanings composed of Subjects, Predicates, Objects, and Description. The fourth Semantic is knowing the meanings or meanings contained in each word in other words. And the Fifth Pragmatics is to use polite language in the right situations. And the results of the five aspects of language development in basic age children that almost all indicators are very well achieved. Only indicators of pragmatic development are still sufficient or are beginning to develop. As for the overall results of the development of the language knowledge of children of basic age in MI Ma'arif Sambego, it can be said to be very good or already achieved